The glycocalyx may play an important role in Preventing Sepsis Campaign in China (PSCC) - Chai, Yan; Fang, Yi-Peng; Zhang, Zhen-Yu; Guo, Zhe; Zhang, Hui-Juan; Wang, Xue-Song; Liao, Hai-Yan; Wang, Zi-Wen; Wang, Zhong (Global Journal of Medical and Clinical Case Reports, 2021)
Sepsis is a common clinical emergency and critical illness, whose prevention and treatment are mainly to protect organ functions. Glycocalyx is a polysaccharide-protein composite structure on the surface of endothelial cells, which has the functions of protecting cell barriers and maintaining organ perfusion. It may protect the organ function, and prevent the infected patients from progressing to sepsis by monitoring of glycocalyx in the serum. This article mainly summarized the cause of PSCC and the possible role of glycocalyx in PSCC to provide reference for clinical intervening.